Period 2 Regulates CYP2B10 Expression and Activity in Mouse Liver - Chen, MengLin; Chen, Min; Lu, Danyi; Wang, Yi; Zhang, Li; Wang, Zhigang; Wu, Baojian (Frontiers in Pharmacology, 2021)
CYP2B10 is responsible for metabolism and detoxification of many clinical drugs. Here, we aimed to investigate a potential role of Period 2 (PER2) in regulating expression of hepatic CYP2B10. Regulatory effects of PER2 on hepatic expression of CYP2B10 and other enzymes were determined using Per2-deficient mice with exons 4-6 deleted (named Per2Del4-6 mice). In vitro and in vivo metabolic activities of CYP2B10 were probed using cyclophosphamide (CPA) as a specific substrate. Regulatory mechanism was investigated using luciferase reporter assays. Genotyping and Western blotting demonstrated loss of wild-type Per2 transcript and markedly reduced PER2 protein in Per2Del4-6 mice. Hepatic expression of a plenty of drug-metabolizing genes (including Cyp2a4/2a5, Cyp2b10, Ugt1a1, Ugt1a9, Ugt2b36, Sult1a1 and Sult1e1) were altered (and majority were down-regulated) in Per2Del4-6 mice. Of note, Cyp2b10, Ugt1a9 and Sult1a1 were three genes considerably affected. Decreased expression of CYP2B10 was translated to reduced metabolism and altered pharmacokinetics of CPA as well as attenuated CPA hepatotoxicity in Per2Del4-6 mice. Positive regulation of CYP2B10 by PER2 was further confirmed in both Hepa-1c1c7 and AML-12 cells. Based on luciferase reporter assays, it was shown that PER2 regulated Cyp2b10 transcription in a REV-ERBα-dependent manner. REV-ERBα was negatively regulated by PER2 (increased REV-ERBα expression in Per2Del4-6 mice) and itself was also a repressor of CYP2B10. In conclusion, PER2 positively regulates CYP2B10 expression and activity in mouse liver through inhibiting its repressor REV-ERBα.